Introduction to dossierCommunity strategies for confronting socio-environmental conflicts: beyond resistance - Karolien van Teijligen; Emilie Dupuits (Íconos)
Introduction to dossierCommunity strategies for confronting socio-environmental conflicts: beyond resistance